The Influence of Information Technology on Company Performance Through Internal and External Integration - Ruth Lovita Surodjo Putri; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2025)
Information technology is essential for companies to make informed decisions that support internal business processes and external collaboration, thereby improving overall company performance. The research collected data from 105 manufacturing companies in East Java. The research sample was determined using judgmental sampling with respondents who were at least staff level and had become permanent company employees. Data analysis was used with SEM-PLS. Implementing information technology in manufacturing companies impacted internal and external supply chain integration. Internal supply chain integration, combined with internal data integration, is running smoothly and in real-time, which positively impacts cross-functional integration and does not directly affect company performance. External supply chain integration, in collaboration with external partners, is progressing well. The company is actively involved in developing these partnerships, which can lead to improved company performance, increased flexibility in meeting customer demands, and reduced production costs. Practical contributions to research provide insight for industry practitioners, enabling the internal cross-functional team to operate in an integrated manner and necessitating collaboration with external parties. Purchasing and marketing managers can play an active role in enhancing the involvement of external partners in improving company performance, making a theoretical contribution to enriching the development of information technology systems, and sustainable supply chains.